Analysis of the Determinants of Revenue in Ornamental Plant Businesses in the East Denpasar District of Denpasar City - I Komang Wibawa; Ni Nyoman Yuliarmi (Transpublika Publisher, 2025)
Ornamental plants are a category of horticultural crops used for their beauty and function, unlike other agricultural commodities used for food production. Denpasar City, in Bali Province, is a prominent producer of ornamental plants, particularly in the East Denpasar District, the city's epicenter. The district specializes in two kinds of ornamental plants: cut orchids and tuberose.The demand for ornamental plants is resilient and driven by new trends. The environment is challenging for ornamental plant business performers in Denpasar City. The objective of this research is to examine the simultaneous and partial influence of business capital, labor, working hours, income level, and regional origins on the revenue of ornamental plant business performers in East Denpasar District. A sample of 80 respondents was utilized, and multiple regression analysis techniques were employed. The research's findings that business capital, labor, working hours, education level, and region origin have a significant effect when considered simultaneously (f). While the partial test results (t) state that business capital and labor have a positive and significant effect on revenue, while working hours and education level partially have no positive effect and are unable to significantly increase revenue, and regional origins partially is statistically insignificant to increase the revenue of ornamental plant businesses in East Denpasar District of Denpasar City.